[Storage Structure at Geothermal Plant] - Streng, Evelyn Fiedler (1975)
Photograph of a storage structure at a geothermal plant. The structure is made of a grey, stone base and central pillar under a circular, blue, metal roof. White pillars surround the central pillar along the stone base. A group of people stand along a dark rock wall and steam. White, rectangular buildings are visible in the background along hills.